The Development of Mild Combustion Open Burner Experimental Setup - M. M., Noor; Andrew P., Wandel; Talal, Yusaf (2013)
This paper discusses the development of the combustion furnace for the Moderate and Intense Low oxygen Dilution (MILD) combustion. The development was started with using Computational Fluid Dynamics (CFD) software. ANSYS Fluent was used to simulate preliminary designs for the burner before the final design sent to workshop to build it. The requirement of MILD combustion are air fuel mixture preheat and dilute the oxygen content in the oxidant stream. In order to achieve this condition, Exhaust Gas Recirculation (EGR) was utilised. The burner requirement is in non-premixed and open burner. To capture and used the exhaust gas, the burner was enclosed with large circular shape wall with open at the top. External EGR pipe was used to transport the exhaust gas and mixed with the fresh oxidant (normal air or syntactic air). Butterfly valve was installed at the top opening as damper to close the exhaust gas flow at the certain ratio for EGR and exhaust out to atmosphere. This damper must be long enough to prevent from backflow of normal air into the combustion chamber. The R-type and K-type thermocouple wire was used to measure the temperature inside the combustion chamber and the EGR pipe. The lambda and gas sensor was installed to measure the gas ompositions. Data acquisition system used to collect the temperature and gas compositions in combustion chamber, EGR pipe and exhaust gas. Three high temperature glass windows (fused silica) were installed to view and capture the image of the flame and analysed the flame propagation. The furnace development completed and ready to be tested.